Inventory Continuous Model and Discrete in Economic - Aidawayati Rangkuti (Jurnal Matematika, Statistika dan Komputasi, 2015)
The available of continuous and discrete model, illustrate the market effect in determination of volume and market price. This effect explains the average convergen and oscilation by determination the parameter exist before. Comparing to Cobweb with discrete model result the equilibrium while Cobweb with continuous  model will have equilibrium where supply and demand price is the same.